Influential factors of online purchase intention in the financial industry: A perspective from an emerging economy - Wen , Shimei (Asian Journal of Economics and Empirical Research, 2025)
This study addresses the gap in understanding the impact of product types on online purchasing decisions in the financial industry. It examines how key factors—product features, financial needs, institutional reputation, and government regulations—affect online purchase intention while also investigating the mediating roles of consumer perceptions. Data from 218 respondents in China was collected via a structured questionnaire distributed across various social media platforms. Quantitative analysis was employed to explore the direct effects of influential factors on online purchase intention, along with the mediating effects of perceived value and purchase risk. The study reveals that product features, financial needs, institutional reputation, and government regulations positively influence online purchase intention in the financial sector. Perceived value amplifies these effects, while purchase risk attenuates them, underscoring the significant mediating role of consumer perceptions. Managers in the financial sector should prioritize brand building and real-time customer engagement to bolster online purchase intentions. Strengthening institutional reputation and highlighting product value can positively sway consumer decisions. Policymakers are advised to enact regulations ensuring e-commerce transaction safety, fostering consumer trust and a secure online purchasing environment.